A Case of Dissociative Seizures Presented like Myoclonic Epilepsy. Issue 2 (25th July 2018) - Reddy, Balaswamy; Das, Soumitra; Ali, Mustafa; Guruprasad, Srinivas
Abstract : Psychogenic seizures are often underdiagnosed and epilepsy is very often over-treated which leads to multiple financial, social and stigma related difficulties. The myoclonic seizure itself is a rare phenomenon and when functional movement disorder presents like myoclonus then it's extremely difficult to pinpoint the exact cause. Here, we are presenting a case who was misdiagnosed as having a myoclonic seizure disorder and treated in multiple places without any improvement which ultimately turned out to be functional movement disorder of a rare variety.